Support to Civil Service Reform in Indonesia : Report from a Programming Mission to Jakarta - World Bank (Washington, DC, 2013)
Civil service reform in Indonesia is needed to sustain the important institutional reform results achieved over the last ten years in various sectors and policy areas and to further consolidate Indonesia as a progressing middle income country. This report summarizes a mission to Indonesia on February 2-13, 2009. The purpose of the mission was to i) map, describe and assess current approach and status of ongoing civil service reform initiatives in selected central government institutions; ii) make recommendations related to scope, focus and approach of continued reforms; and iii) propose to the Government of Indonesia (GOI) a World Bank program of assistance in support of the government's reform agenda. The report is intended to provide a basis for a decision within the Bank on whether and how to continue and scale up an engagement on civil service reform in Indonesia. Aligned with the three objectives, the mission report first provides an introduction to the political economy of civil service reform in Indonesia and an overview and profile of ongoing reform initiatives. It then analyses key civil service challenges, using the dimension in the draft framework for Actionable Governance Indicators as a point of departure. Finally, a possible program for donor support is presented in light of the analysis of key challenges and the political economy of reform.